2013
DOI: 10.1177/1758834013500702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development of S-1 for non-small cell lung cancer: a Japanese perspective

Abstract: For more than a decade, S-1 has been investigated aggressively against non-small cell lung cancer (NSCLC) in Japan. Recently, two randomized phase III trials of S-1 combined with cisplatin (CDDP) or carboplatin (CBDCA) compared with the standard platinum doublet chemotherapy were reported. S-1 and CDDP was noninferior to CDDP and DTX in terms of overall survival (OS) (median survival time [MST] 16.1 versus 17.1 months, respectively; hazard ratio [HR] 1.013; 96.4% confidence interval [CI] 0.837-1.227). Noninfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…S-1 is an oral 5-fluorouracil (5-FU) derivative that is widely used for the treatment of various solid tumors, including NSCLC [5]. Recently, a phase 3 study of S-1 monotherapy demonstrated non-inferiority compared with docetaxel in patients with NSCLC; thus, S-1 is considered a standard chemotherapy option in East Asia [6].…”
Section: Introductionmentioning
confidence: 99%
“…S-1 is an oral 5-fluorouracil (5-FU) derivative that is widely used for the treatment of various solid tumors, including NSCLC [5]. Recently, a phase 3 study of S-1 monotherapy demonstrated non-inferiority compared with docetaxel in patients with NSCLC; thus, S-1 is considered a standard chemotherapy option in East Asia [6].…”
Section: Introductionmentioning
confidence: 99%
“…TS-1 combined with cisplatin or carboplatin has been studied for NSCLC. The result showed that the regimen is similar to cisplatin plus doxetaxel or carboplatin plus paclitaxel (Takeda, 2013). However, platinum combined 3rd generation chemotherapeutic agents is the standard of care for non-small cell lung cancer, which mad platinum not available in later line chemotherapy regimen (Fossella et al, 2003; Gao et al, 2009; Genova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…is an antimetabolite that is widely used to treat various solid cancers including nonsmall cell lung cancer (NSCLC). 1,2 In Japan, an oral 5-FU prodrug has been developed. At present, UFT® and TS-1® are indicated in Japan for NSCLC and are often used as one of the drugs in postoperative adjuvant chemotherapy or systemic chemotherapy.…”
mentioning
confidence: 99%
“…In addition, 5-FU anticancer agents are less effective in patients with advanced or recurrent NSCLC. 2 However, if the therapeutic effect of 5-FU anticancer drugs in cancer patients can be predicted before administration, the disadvantages of unnecessary administration can be prevented. Thus, identi cation of factors that can predict the effect of drugs before drug administration is important.…”
mentioning
confidence: 99%